Non-trivial uses of melatonin: Its effects on sleep, jet lag, obesity, migraine, and gastrointestinal disorders - Wirkijowski, Jakub; Wirkijowska, Małgorzata; Mędyk, Jolanta; Patarocha, Yauheniya; Rogulski , Michał; Ślusarska , Aleksandra; Błasiak , Paulina; Mikołajec, Patryk; Huk, Ruslan; Bilecka, Barbara (Journal of Education, Health and Sport, 2025)
Introduction and aim of the study: Melatonin consumption is steadily increasing. In this literature review, the authors intended to introduce the latest scientific evidence on the influence of the sleep hormone not only on the quality of time spent in bed and jet lag, but also to consider possible other positive impacts. Its eventual effects on headaches, gastrointestinal complaints, or obesity were analyzed. Materials and methods: The authors searched the scientific literature utilizing search engines such as Science Direct, Cochrane, PubMed, Google Scholar, and UpToDate. The literature review focused on the association of melatonin with issues such as sleep, migraines, GERD, IBS, and jet lag. Results: Most of the articles reviewed in this study highlighted the positive effects of melatonin supplementation on sleep problems and jet lag. Furthermore, many studies report that it likewise has a beneficial impact on conditions not directly related to sleep, such as obesity, GERD, IBS, or migraine. Nevertheless, the articles emphasize the need for further research to establish treatment protocols and to select an optimal dose.